Mental Well-Being of Boarding Students Versus Family-Living Students: Links with Academic Engagement and Self-Compassion - Asiyah, Dewi; Mahmudah, Mahmudah; Saepulah, Aep; Perdana, Fani Juliyanto (KONSELOR, 2025)
The increasing number of boarding students reflects broader educational demands that require adolescents to live away from their families. Boarding students often encounter different psychosocial environments than family-living students, which may shape their experiences of stress and social support. This study aimed to examine the association between perceived stress and social support among boarding students. A cross-sectional quantitative design was employed with 295 participants recruited from senior high schools. Data were obtained using the Perceived Stress Scale (PSS) and the Multidimensional Scale of Perceived Social Support (MSPSS). Statistical analyses showed that boarding students reported significantly higher stress compared to family-living students, t(293) = -4.215, p < .001. Stress was negatively associated with social support, r = -.472, p < .001, indicating that students with higher support tended to experience lower stress. These findings underscore the importance of fostering supportive networks for adolescents living away from home. Practical implications suggest that schools and caregivers can implement targeted programs to strengthen social resources, thereby promoting student well-being in boarding settings.